2012
DOI: 10.1590/s1678-77572012000300014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of concentration, time and method of application of citric acid and sodium citrate in root conditioning

Abstract: ObjectiveThe aim of this study was to establish the parameters of concentration, time and mode of application of citric acid and sodium citrate in relation to root conditioning. Material and MethodsA total of 495 samples were obtained and equally distributed among 11 groups (5 for testing different concentrations of citric acid, 5 for testing different concentrations of sodium citrate and 1 control group). After laboratorial processing, the samples were analyzed under scanning electron microscopy. A previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
6
0
4
Order By: Relevance
“…The traditional treatment of periodontally compromised roots have relied on mechanical instrumentation (1-4) that is not able to fully eliminate the infection due the formation of a smear layer of organic and mineralized debris (3)(4)(5)(6). As a compensation for these limitations of mechanical therapy; chemical root conditioning has been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional treatment of periodontally compromised roots have relied on mechanical instrumentation (1-4) that is not able to fully eliminate the infection due the formation of a smear layer of organic and mineralized debris (3)(4)(5)(6). As a compensation for these limitations of mechanical therapy; chemical root conditioning has been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…6 The use of low pH acting agents has been challenged, as their use might be detrimental to the surrounding vital periodontal tissues and may interfere with healing after the regenerative procedures. 7 Studies have shown that ethylene diamine tetra acetic acid (EDTA), a chelating agent which can act at neutral pH is preferable over the other acid solutions because it preserves the integrity of surrounding periodontal tissues along with root surface demineralization and smear layer removal. 8 With this background, a scanning electron microscopic (SEM) study was designed to evaluate and morphometrically analyze the demineralizing efficacy of an EDTA solution at lower concentration (15% and pH 7.4) with that of a tetracycline hydrochloride solution (pH 1.8), on root surfaces of periodontally involved tooth.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, estudos in vitro (KIESWETTER et al, 1996;MARTIN et al, 1995) e in vivo (BUSER et al, 1991;COCHRAN et al, 1996) (RUGGERI et al, 2007) mas, em contrapartida, foi verificada destruição da estrutura do colágeno exposto por ácido cítrico em concentrações muito baixas (entre 0,5 % e 2 %) e por tempos muito longos como 3 minutos (CAVASSIM et al, 2012). Entretanto, foi demonstrado que a desmineralização de dentina com ácido cítrico até 2 minutos mantém intactas as moléculas de colágeno tipo I e de sulfato de condroitina em nível ultraestrutural (RUGGERI et al, 2007;FEIST et al, 2003).…”
Section: Samira Salmeron Resultadosunclassified